Indomitable spirit - Abdul Kalam, A. P. J. (Avul Pakir Jainulabdeen), 1931- (New Delhi : Rajpal & Sons, 2006)
Collections of President Abdul Kalam's speeches and addresses on diverse topics.
Includes bibliographical references (p. 246-254).
Keywords: Abdul Kalam, A. P. J. -- 1931-; Presidents -- India; Speeches, addresses, etc